KEGIATAN BERKELANJUTAN PEMBINAAN KESADARAN HUKUM DAN PEMBERDAYAAN DIRI MASYARAKAT DALAM PERSPEKTIF PENTINGNYA BERAKHLAK MULIA DI POLRES METRO JAKARTA UTARA - Mumpuni, Sri; Maria, Kiki; Istiqomah, Istiqomah; Tarmudi, Tarmudi (MAJU : Indonesian Journal of Community Empowerment, 2025)
In relation to the role and purpose of community service, especially for prisoners at the North Jakarta Metro Police as mentioned above, there is an interesting phenomenon that has been implemented by a team of lecturers from Bung Karno University Jakarta by formally organizing a Community Service program in the prisoners' meeting room with the theme "Ongoing Activities for Legal Awareness Development and Community Empowerment in the Perspective of the Importance of Noble Morals at the North Jakarta Metro Police" on Wednesday, June 11, 2025 as a means of development and empowerment for these prisoners. The demands of economic life and the lack of skills in empowering themselves make it difficult to get decent work to meet their living needs. In this regard, moral values ​​greatly influence these things. This factor is one of the triggers for carrying out various methods including deviant actions that violate the law.